La tecnología y el carácter de la notificación personal frente al principio de publicidad (2022)
Colombia has made a transition in the last 10 years from a stagnant State to an efficient one in the use of technological means, which has caused changes in the procedure, specifically in the notification mechanism of the administration's decisions; although the regulations and academic research maintain that personal notification is the ideal mechanism to make the principle of publicity effective, primarily due to the low access that the population has to the internet and digital media. Given the little analytical work that documents the objective knowledge of the primacy of personal notification over electronic, this research addresses this gap from the study of regulations, doctrine, and national and other countries' jurisprudence. Seven public entities were asked about the implementation of electronic notification, in order to establish whether, at present, the use of technologies has displaced the main character of personal notification and if this violates the principle of publicity. It was determined in the findings that the personal notification is being displaced by the electronic medium and that the principle of publicity is guaranteed through contracting with companies that certify the authenticity of the notification.